ARUTMIN’S CSR FOOTPRINT IN THE SDGS: PROMOTING INCLUSIVE HEALTH IN THE KINTAP MINING AREA - Hadrianti H. D. Lasari; Astrid Rudyanto; Desi Adhariani; Abdillah Ahsan; Deasy Ariyanti Rahayuningsih (Universitas Pelita Harapan, 2025)
Responsibility (CSR) initiatives, such as maternal and child health check-ups, elderly health services, youth education, and HIV/AIDS awareness campaigns. These community service activities aim to improve public health quality in the mining area through participatory and collaborative approaches. The implementation process begins with assessing community needs through interviews and Focus Group Discussions (FGDs) involving community leaders, religious figures, and local stakeholders. The results indicate improved access to basic health services, positive changes in healthy living behaviors, and strengthened relationships between the company and the local community. This program contributes to achieving the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), and SDG 17 (Partnerships for the Goals). The community service initiative serves as a model for locally based and sustainable health interventions.